Spatial Dynamics of the Financial Kuznets Curve in the European Union - Özek, Yavuz; Taşar, İzzet; Bayat, Tayfur (Sosyoekonomi Society, 2026)
In this study, the validity of the Financial Kuznets Curve (FKC) in the EU-27 economies for the period 2009-2022 is examined using geographically weighted regression (GWR). According to the results of Global Moran’s I and LISA, there is strong, positive, and significant spatial dependence both in the variables and in the residuals of the ordinary least squares (OLS) model. When comparing the performance of various coefficient-of-determination metrics based on the lambda coefficient, the validity of the FKC is primarily determined by the country's location. From the perspective of the global OLS model, the FKC hypothesis is not valid. According to the GWR results, the FKC is valid in Ireland, Portugal, Spain, France, Romania, Hungary, Bulgaria, and Croatia. While inflation reduces income inequality in Portugal and Belgium, it increases income inequality in France, Germany, Malta, Italy, Czechia, Slovakia, Greece, Bulgaria, Romania, Croatia, Lithuania, Latvia, and Estonia. Trade openness reduces income inequality in Poland, Hungary, Slovakia, Latvia, and Croatia; however, it has an increasing effect in Finland and Luxembourg. As a result, because the FKC hypothesis exhibits strong spatial dependence across EU-27 countries, it is valid only in certain countries. Therefore, instead of uniform solutions in the design of economic policy, policy packages should be developed that are tailored to the institutional structure of financial markets, price dynamics, and foreign trade structures of the countries. © 2026, Sosyoekonomi Society. All rights reserved.
Avrupa Birliği’nde Finansal Kuznets Eğrisinin Mekânsal Dinamikleri
Keywords: European Union; Financial Kuznets Curve; Geographically Weighted Regression